2009
DOI: 10.1080/10790268.2009.11760769
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Rolipram Increases Medullary and Spinal cAMP and Activates a Latent Respiratory Motor Pathway After High Cervical Spinal Cord Injury

Abstract: Background/Objective: High cervical spinal cord hemisection interrupts descending respiratory drive from the rostral ventral respiratory group in the medulla to the ipsilateral phrenic motoneurons. Hemisection results in the paralysis of the ipsilateral hemidiaphragm. Chronic administration of rolipram, a specific phosphodiesterase-IV inhibitor, promotes synaptic plasticity and restores phrenic nerve function after a high cervical spinal cord lesion. Here, we test the hypothesis that an acute administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…Conversely, A 2A or 5-HT 7 receptor agonists may be useful to restore respiratory and non-respiratory (somatic) motor function following spinal injury (Golder et al 2008) or motor neuron disease by eliciting spinal plasticity. Factors that activate cAMP-PKA may trigger functional recovery (Kajana et al 2008; 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, A 2A or 5-HT 7 receptor agonists may be useful to restore respiratory and non-respiratory (somatic) motor function following spinal injury (Golder et al 2008) or motor neuron disease by eliciting spinal plasticity. Factors that activate cAMP-PKA may trigger functional recovery (Kajana et al 2008; 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Rather, theophylline causes a specific change in the respiratory circuitry that allows for a persistent expression of the CPP after the animal is weaned from the drug. The underlying mechanisms for this drug-induced plasticity in the respiratory circuitry have been the subject of recent investigations in the Goshgarian laboratory (Kajana and Goshgarian, 2008a, 2008b, 2009). …”
Section: Drug-induced Plasticity In the Crossed Phrenic Pathway: Tmentioning
confidence: 99%
“…It has been demonstrated that rolipram (2.0 mg/kg, i.v.) activated the phrenic nerve discharge by increasing the cAMP content in the medulla oblongata and cervical spinal cord after high cervical spinal cord injury in rats [16]. Moreover, rolipram (0.1-5 μM) recovered depression of the respiratory-related rhythm induced by opioids in vitro [32,33].…”
Section: Inhibition Of Pde4 Relieves Morphine-induced Ventilatory Depmentioning
confidence: 96%